Telepsychiatry care during the COVID-19 outbreak in young adults with a first episode of psychosis or entering schizophrenia. (13th April 2021) - Kiesmann, E.; Mallet, J.; Charlot, V.; Dubertret, C.
Abstract : Introduction: During the Covid Outbreak, the deployment of psychiatric phone-based consultations (PbC) became a large necessity. Objectives: The main objective of our study was to assess, 4 months after the end of the lockdown, the degree of satisfaction of the PbCs compared to that of usual face-to-face consultations (FC) in young adults presenting a first episode of psychosis (FEP) or entering schizophrenia (SCZ). Methods: All patients beneficiated from PbCs conducted by hospital care staff during lockdown. A 15-items questionnaire evaluating satisfaction was carried out remotely (score ranging from 1 to 10). Primary outcome was satisfaction with consultation allowing the comparison of a group preferring FC (FC+) against a group in favor or equivalent of PbC (PbC +). Results: 30 patients were recruited (mean age 26.93 years old (4.9 SD), Male 56%. Diagnoses were SCZ 60% and FEP 40%. 20/30 participants belonged to (FC+) group. Total scores of satisfaction for the PbC differed between the (PbC+) group (mean 9 (1.69 SD)) and (FC+) group (mean 6.80, (1.32 SD)) p < 0.05. The (FC+) group tends to have PbC more frequently (40%) than the (PbC+) group (10%) and to find the phone interface more stressfull (40%) than the PbC+ group (10%). The (FC+) group tends to less wish (40%) PbC follow up in future than the (PbC+) group (90%). Conclusions: This study shows that the PbCs were favorably evaluated by a third of the patients. The anxiety-inducing experience of the PbC in the (FC+) group could be explained by the severity of their pathology.